A Successful Heat Wave Prevention in Ahmedabad Calls for Segregated Health Record: Highlights from Existing Heat Action Plan - Priya Dutta; Prashant Rajput; Polash Mukherjee; Prima Madan; Dileep Mavalankar (Aerosol and Air Quality Research, 2022)
Abstract South Asia is one of the hot-spots of extreme heat events and associated health risks. As heat waves continue to get harsher due to climate change, South Asia’s exposure to them is probably going to increase. After a heatwave in 2010, Ahmedabad implemented South Asia’s first heat action plan (HAP). The Ahmedabad HAP can serve as a model for other cities across South Asian nations interested in intervention strategies against excessive heat. In recent years, 2020 and onwards, Ahmedabad’s healthcare system faces an extreme COVID-19 crisis which resulted in severe negligence of heat wave-influenced mortality and morbidity cases. Though the city continued to disseminate the necessary information for public heat preparedness from the existing heat action plan, there was no record made separately for COVID-19 and heat stress-related mortality/morbidity by the health department. Thus, due to a lack of heat-related health records, we were unable to track the HAP intervention effect in 2022.